Ethnobotany Research and Applications: Required standards for manuscripts based on field research - Yebouk, Cheikh (Ethnobotany Research and Applications, 2025)
Ethnobotany Research and Applications (ERA), established in 2003, has consistently adhered to its mission of providing free, open-access, and rapidly published research materials worldwide. Over more than 20 years, ERA has grown significantly, publishing nearly 30 volumes and expanding its scope to include ethnobiology, ethnomycology and ethnozoology. Initially hosted at the University of Hawaii, it is now managed by Ilia State University in Georgia and indexed in Scopus and Crossref. With a CiteScore of 3.4 and an acceptance rate between 13-18%, the journal has achieved high academic standing in various fields. Submissions have quadrupled over the last years, with improved publication timelines, but many manuscripts need to be rejected due to failure to follow author guidelines, poor formatting, language issues, etc. ERA faces recurring issues in submissions, including exaggerated claims about medicinal plant studies, misuse of statistical methods, and confusion between "use" and "knowledge." Many authors also neglect core botanical requirements such as proper species identification and vouchering, undermining reproducibility. The journal remains committed to its free and open-access model, supported by Ilia State University, an unpaid editorial team, and voluntary reviewers. Authors and readers are urged to participate in the peer-review process to sustain ERA's operations and uphold its standards of excellence. Ethnobotany and ethnopharmacology provide invaluable insights into the relationships between plants and human cultures, especially regarding traditional knowledge, medicinal practices, and sustainable resource use. The Ethnobotany Research and Application Journal embraces this interdisciplinary field, promoting high-quality submissions that meet methodological rigor and align with global ethical standards. The editorial team recognizes that the volume of submissions often exceeds the journal's publication capacity. Therefore, ensuring adherence to specific methodological and ethical standards is critical for manuscript acceptance. This article serves as a guideline for authors to align their submissions with these requirements. Drawing inspiration from similar standards established in other journals, this document outlines essential criteria for manuscripts focusing on field-based ethnobotanical research